Museum perceptions and productions: American migrations of a Maori hei-tiki. Issue 1 (March 2016) - Kohlstedt, Sally Gregory
Abstract : Museum objects have biographies shaped by their material, geographical and cultural origins, their initial intended purpose, and the ways in which they are valued and interpreted by curators and public audiences. Often one object becomes highly symbolic of a particular group even as its presentation over time reflects changing perceptions of the culture as well as the individual object. A Maori hei-tiki – a small but distinctive greenstone pendant – collected by Charles Wilkes on his United States Exploring Expedition in 1840 provides insight into changing museum practices, museum networks of exchange, the impact of professionalizing expertise in ethnology and anthropology since the late nineteenth century, shifting public interests and expectations, and, indeed, the unanticipated ways in which museum objects find their way into exhibition, in this case at the Smithsonian Institution. The material resilience and embedded historicity of the hei-tiki remain as a counterbalance to its versatility as an object useful in multiple stories over nearly two centuries.